ANALISIS POTENSI MASYARAKAT â€œUMA LENGGEâ€ DI DESA MARIA WAWO KABUPATEN BIMA SEBAGAI DESA WISATA (TOURISM VILLAGE) - Argubi, Adi Hidayat; Ramadhoan, Ruli Inayah; Tauhid, Tauhid (Universitas Muhammadiyah Jember, 2019)
AbstractThe purpose of this research is to find out the various potential attractions of the Uma Lengge tourist attraction Maria Wawo Village in Maria Village, Wawo Bima sub-district as a tourist village. This type of research used in this research is descriptive research. This research was conducted in Maria Village, Wawo Sub-district, Bima District. The stages of data collection are observation, structured interviews, questionnaires, and literature study. While the data analysis method used is descriptive qualitative, SWOT, and value scale analysis. The results showed that the potential of Wawo Tourism Village as one of the attractions in Bima Regency was physical potential that included